Taxonomy of the Genus Sargassum (Fucales, Phaeophyceae) from Alabat Island, Quezon, Northeastern Philippines - Santiañez, Wilfred John E.; Trono Jr., Gavino C. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 25 No 1 (2013), 2013)
Taxonomic observations on some Sargassum species in Alabat Island, Quezon are presented. These are based on collections made on the spot during an ecological survey on the Sargassum-dominated seaweed communities in the locality. Gross morphological characteristics of the species such as the type of holdfast, shape and nature of its branches, vesicles, leaves, nature and distribution of cryptostomata, and nature and form of receptacles were used to discriminate the different morphotypes. Free-hand sections of receptacles were made to ascertain the sex of the plant. Different morphotypes were identif ied up to species level when possible. Eight morphotypes were distinct, six of which were recognized, namely, Sargassum crassifolium J. Agardh, S. cristaefolium C. Agardh, S. kushimotense Yendo, S. gracillimum Reinbold, S. myriocystum J. Agardh, and S. polycystum C.A. Agardh. The two other remaining materials were unidentified and are described here in detail. Keywords: Sargassum, brown seaweed, seaweed taxonomy, diversity, Philippines